The impact of sinkholes on species richness and diversity: implications for mine rehabilitation - Keiller, Bronwen May (My University, 2011)
Mining often results in numerous detrimental impacts on the surrounding environment. One such potential impact is the formation of sinkholes on mining property, commonly resulting from dewatering operations initiated by mines to keep working conditions dry and safe. The rehabilitation of these sinkholes poses problems for mines that near closure; not only because of the potential costs involved, but also in determining the best methods to rehabilitate a sinkhole. In order to determine the best rehabilitation requirements the differences in biodiversity found between sinkholes and the surrounding area were examined. Two sinkholes and the areas surrounding each sinkhole were sampled for small mammals, reptiles, amphibians, invertebrates. Basic vegetation and environmental variables studies were also conducted. Grass cover was significantly higher than all other environmental variables (woody, forbs, rock, bare ground and plant litter cover) outside the sinkhole. Inside the sinkholes plant litter, grass and rock cover were significantly higher than the other environmental variables. Woody cover was significantly higher inside the sinkholes, compared to woody cover outside the sinkholes. The average percentage cover of broad-leaved plants was significantly lower than narrow‐leaved plants outside the sinkholes. The cover of broad leaved plants outside the sinkholes was significantly lower in comparison to cover inside the sinkholes. No significant differences were recorded between different seed dispersal types outside the sinkholes. However, inside the sinkholes, the average percentage cover of plants with other types of seed dispersal was significantly higher than animal dispersed seed types. The floral composition analyses found that Tagetes minuta featured prominently inside the sinkholes, while Digitaria longiflora was the most important species outside the sinkhole. The multivariate analysis showed a certain degree of separation between inside and outside quadrats, based on the environmental variables studied. A total of six animal classes were recorded in the study sites. Insecta were most abundant both outside and inside the sinkholes. Outside the sinkholes, Insecta were significantly higher than Arachnida and Myriapoda. Amphibians were significantly lower than all other animal classes. Inside the sinkholes, Insecta and Arachnida were significantly higher than Mammalia and Reptilia. The sinkholes examined in this study do not appear to have decreased levels of biodiversity, but rather present altered environmental conditions to those found outside the sinkholes, allowing the establishment of different species. The exclusion of fire, grazing and frost from sinkholes are likely to be contributing factors in the different growth type abundances and may also impact on invertebrate abundances. The environmental conditions inside the sinkhole that differ from surrounding conditions may be preferred by certain species, while they are avoided by others. Faunal species appear to exhibit individual preferences on sinkhole selection based on their life strategies. Given sufficient time it would appear that sinkholes regenerate to sufficient levels that allow ecosystem functioning. As a result of this, it may not be necessary to refill sinkholes unless out of safety concerns. Only a limited number of variables were examined in this study and future work is required to justify the findings and explanations given herein. Additional environmental variables, such as slope, and detailed studies on the exact differences in moisture, humidity, sunlight, temperature etc. between the sinkholes and surrounding areas should be included in further studies. Both the grazing and burning regimes of the sinkholes and surrounding areas should be established to provide further insight and understanding in the differences between sinkholes and the surrounding areas.